Alto Ribeirão geosystem: anthropogenic derivations in space-time - Gonçalves, Pedro Henrique Ribeiro (2025)
This report aims to carry out a qualitative geosystemic analysis of the Alto Ribeirão territory, focused on the structural, spatial, dynamic and functional aspects of the landscapes. In this way, we hope to know anthropogenic derivations in space and time and understand the different levels of environmental weaknesses, accentuated by the capitalist model of land use and occupation. The choice for this geographical area was made taking into account its territorial configuration and the social dynamics that are now under construction at an accelerated urban pace, but are very marked by its historical movement and the social relations that produced its space over a long period with eminently rural characteristics.